The uncompromising partners: The theory of breakdown of marriage and the adversarial judicial procedure - Wijeyesekera, Rose (My University, 2011)
The rigours of the fault-based divorce law have neither prevented the breakdown of marriages nor the divorce of married couples. In its failure to identify the actual causes and reasons which motivate a couple to seek a divorce, the law has created a lacuna between legality and reality. One of the main objectives of introducing matrimonial fault as the basis for divorce was to impose strict limits on the potentiality of dissolving marriage. In a fault-based divorce system, the law is expected to act as a buttress to preserve the legal tie of marriage. This legal bolstering may have been vital in a social context where marriage was considered as a sacrament. Since the fault-based law allows dissolution of marriage only on proof of certain recognized facts, an adversarial judicial procedure is somewhat suited. In the combination of matrimonial fault and adversarial procedure, a marriage is not dissolved unless it is proved to the satisfaction of the court that the defendant is guilty of a legally prohibited act, even though it is clearly evident to the court that the marital relationship between the spouses has broken beyond repair.